2018
DOI: 10.36076/ppj.2018.1.e49
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Smoking is Not Associated with Increased Postoperative Opioid Use in Patients with Lung Cancer or Esophageal Cancer

Abstract: Background: Chronic smokers show differences in pain sensitivity compared to healthy non-smokers. Yet, no study to date has examined whether smoker status has an effect on postoperative pain. Objective: We aim to examine a possible correlation between preoperative smoking and postoperative opioid dose based on the hypothesis that smokers would use higher doses of opioids to manage increased postoperative pain. Study Design: A retrospective observational cohort study. Setting: The National Cancer Center in Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…This ratio could not be calculated for nalbuphine as response rate did not decrease as a function of nalbuphine dose. 2002; Kyte et al, 2018) and nicotine-opioid interactions (Patterson et al, 2012;Kishioka et al, 2014;Plesner et al, 2016;De Vita et al, 2019), the use of nicotine to promote opioid antinociception has not yet been systematically evaluated clinically, perhaps owing to previous reports of increased opioid use in tobacco users (Skurtveit et al, 2010;Yoon et al, 2015; but see Ackerman, 2012;Oh et al, 2018). However, the present results indicate that nonsmokers might benefit from the use of nicotine as an adjuvant for opioid analgesia, an idea that is supported by clinical data obtained in nonsmokers.…”
Section: Nicotine As An Opioid Adjuvantsupporting
confidence: 62%
See 1 more Smart Citation
“…This ratio could not be calculated for nalbuphine as response rate did not decrease as a function of nalbuphine dose. 2002; Kyte et al, 2018) and nicotine-opioid interactions (Patterson et al, 2012;Kishioka et al, 2014;Plesner et al, 2016;De Vita et al, 2019), the use of nicotine to promote opioid antinociception has not yet been systematically evaluated clinically, perhaps owing to previous reports of increased opioid use in tobacco users (Skurtveit et al, 2010;Yoon et al, 2015; but see Ackerman, 2012;Oh et al, 2018). However, the present results indicate that nonsmokers might benefit from the use of nicotine as an adjuvant for opioid analgesia, an idea that is supported by clinical data obtained in nonsmokers.…”
Section: Nicotine As An Opioid Adjuvantsupporting
confidence: 62%
“…It has been reported that nicotine can induce the release of endogenous opioids, and that crosstolerance between nicotine and m-opioid agonists develops, coupled with changes in m-opioid receptor (MOR) expression levels (Kishioka et al, 2000). Some studies suggest that tobacco users are especially sensitive to chronic pain or require higher doses of opioids to manage chronic pain, possibly reflecting nicotineinduced crosstolerance to MOR agonists (Yoon et al, 2015; however, see Ackerman, 2012;Plesner et al, 2016;Oh et al, 2018;De Vita et al, 2019). However, as of 2017, only approximately 14% of the Americans smoked cigarettes (Centers for Disease Control and Prevention, 2018), leaving the possibility that a large nonsmoking population may benefit from nicotine's analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…More smokers underwent VATS compared with non-smokers, and it is therefore important to detect whether the increased risk for postoperative pain was smoking-related actually or if there was other explanations. And in VATS, the association between smoking history and postoperative pain was controversial 25,26 . The multiple analysis of this study indicated that presence of previous history of smoking increased the risk of moderate-severe acute pain following VATS by 86% (OR, 1.86; 95% CI, 1.29 to 2.70, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, accumulating evidence has indicated that cigarette smoking may influence narcotic requirement, pain severity, and the risk of chronic pain after surgery. [11][12][13][14][15][16][17][18][19][20][21][22] However, the association between smoking and opioid consumption or pain intensity is not clear due to conflicting results, with positive associations reported in some studies [11][12][13][14][16][17][18][19][20]22 but not in others. 15,21 In addition, some methodological drawbacks reduced the validity of previous studies, including small sample size (n < 1000), 11,14,[17][18][19][20][21][22] inadequate control for confounding factors, 11,19,22 and restriction to specific types of surgery.…”
Section: Introductionmentioning
confidence: 99%